2011
DOI: 10.1021/om100890q
|View full text |Cite
|
Sign up to set email alerts
|

New Bidentate Trans-Chelating N-Heterocyclic Carbene Ligands for Palladium

Abstract: A family of imidazolium salts of the type [BnN(CH 2 CH 2 CH 2 R Im) 2 ] 3 2[Cl] (Bn = CH 2 Ph; R Im = 1-methylimidazole (1a), 1-tertbutylimidazole (1b), 1-benzylimidazole (1c), 1-methylbenzimidazole (1d)), which contain a tertiary amine linking two imidazolium groups, has been synthesized. These imidazolium salts can be deprotonated with Ag 2 O to generate the Ag carbene complexes 2d)). In the solid state 2d exists as an unusual tetramer, which consists of an [Ag 2 Cl 4 ] 2À core bridging two Ag(NHC) cations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…Complexes of the type [PdCl 2 (NHC) 2 ] are often obtained as mixtures of the cis and trans isomers,20 even with chelating bis(NHC) ligands 21. This is in agreement with results of DFT calculations published by Blakemore et al, which revealed that the trans isomer of [PdCl 2 (NHC) 2 ] is only slightly more stable than the cis isomer 22. The five‐membered NHC complex [PdCl 2 (IBn) 2 ] and the six‐membered analogue [PdCl 2 (THP‐ i Pr) 2 ] adopt a cis and a trans structure, respectively, in the solid state 18,19.…”
Section: Resultssupporting
confidence: 88%
“…Complexes of the type [PdCl 2 (NHC) 2 ] are often obtained as mixtures of the cis and trans isomers,20 even with chelating bis(NHC) ligands 21. This is in agreement with results of DFT calculations published by Blakemore et al, which revealed that the trans isomer of [PdCl 2 (NHC) 2 ] is only slightly more stable than the cis isomer 22. The five‐membered NHC complex [PdCl 2 (IBn) 2 ] and the six‐membered analogue [PdCl 2 (THP‐ i Pr) 2 ] adopt a cis and a trans structure, respectively, in the solid state 18,19.…”
Section: Resultssupporting
confidence: 88%
“…Bulky Mes wingtips prevented associative substitution, which led to the low activity of complex 30 . Later, Hazari and co‐workers prepared four trans ‐chelating complexes, such as 32 , through transmetalation . The trans ‐spanning bis(NHC)‐ligated palladium centers disfavored oxidative addition of the substrate.…”
Section: Homogeneous Catalysismentioning
confidence: 99%
“…Blakemore et al . reported a family of imidazolium salts, which comprise a 3° amine linking two imidazolium groups as shown in Scheme . These imidazolium salts ( L69 ) were deprotonated with Ag 2 O to produce the silver carbene complexes [{BnN(CH 2 CH 2 CH 2 R Im) 2 }Ag]·[AgCl 2 ] ( C113 ), which on reaction with PdCl 2 (MeCN) 2 produces palladium species of the type {BnN(CH 2 CH 2 CH 2 R Im) 2 }PdCl 2 ( C114 ) in 82–96% yields, a rare case of a family of Pd complexes that contain a bidentate trans ‐chelating NHC ligand.…”
Section: N‐heterocyclic Carbenes As Ligands and Their Metal Complexesmentioning
confidence: 99%